2019
DOI: 10.1186/s13046-019-1119-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-96-5p targets PTEN expression affecting radio-chemosensitivity of HNSCC cells

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is the sixth leading cancer worldwide. They are typically characterized by a high incidence of local recurrence, which is the most common cause of death in HNSCC patients. TP53 is the most frequently mutated gene in HNSCC and patients carrying TP53 mutations are associated with a higher probability to develop local recurrence. MiRNAs, which are among the mediators of the oncogenic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 43 publications
3
64
0
Order By: Relevance
“…Chen et al indicated that miR-125b suppresses oral oncogenicity by targeting the anti-oxidative gene PRXL2A (Chen et al, 2019). Numerous studies have found that miR-96-5p not only affected cell proliferation, but was also closely associated with prognosis in cancers including ovarian cancer, HNSCC, hepatocellular carcinoma and colorectal cancer (Liu et al, 2019;Vahabi et al, 2019;Iwai et al, 2018;Ress et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al indicated that miR-125b suppresses oral oncogenicity by targeting the anti-oxidative gene PRXL2A (Chen et al, 2019). Numerous studies have found that miR-96-5p not only affected cell proliferation, but was also closely associated with prognosis in cancers including ovarian cancer, HNSCC, hepatocellular carcinoma and colorectal cancer (Liu et al, 2019;Vahabi et al, 2019;Iwai et al, 2018;Ress et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many human miRNAs have been confirmed to be dysregulated in OSCC, including miR-543, miR-4513, miR-31, miR-223 and miR-125b (Wang et al, 2019;Xu et al, 2019;Kao et al, 2019;Jiang et al, 2019;Chen et al, 2019). Up until now, miR-96-5p had been reported to function as an oncogene in ovarian cancer, HNSCC, hepatocellular carcinoma (Liu et al, 2019;Vahabi et al, 2019;Iwai et al, 2018), or function as a tumor suppressor in colorectal cancer (Ress et al, 2015), the functions of miR-96-5p in OSCC were rarely explored previously. Therefore, we investigated the functional roles and mechanisms of miR-96-5p in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…As for many human cancers, TP53 is the most frequently mutated gene in HNSCC [9,17]. In TCGA dataset, which includes 478 HNSCC molecularly well characterized cases we found that patients carrying TP53 mutation exhibited a signi cantly lower level of TMPRSS2 expression compared to the patients with intact TP53 gene ( Fig.…”
Section: Ace2 and Tmprss2 Expression In Hnscc Patientsmentioning
confidence: 81%
“…As for many human cancers, TP53 is the most frequently mutated gene in HNSCC [ 9 , 19 ]. In TCGA dataset, which includes 478 HNSCC molecularly well characterized cases we found that patients carrying TP53 mutation exhibited a significantly lower level of TMPRSS2 expression compared to the patients with intact TP53 gene (Fig.…”
Section: Resultsmentioning
confidence: 99%